Effect of Remifentanil on Pain and Secondary Hyperalgesia Associated with the Heat–Capsaicin Sensitization Model in Healthy Volunteers - Petersen, Karin L.; Jones, Bruce; Segredo, Veronica; Dahl, Jørgen B.; Rowbotham, Michael C. (Anesthesiology (Philadelphia), 2001)
The heat--capsaicin sensitization model was developed as a noninvasive and noninjurious human experimental pain model. The sequential application of moderate intensity thermal and topical chemical stimuli produces stable and long-lasting areas of cutaneous secondary hyperalgesia. The aim of the present study was to validate the heat--capsaicin sensitization model as a tool for testing analgesic drug efficacy. Responsivity of model-associated measures was tested with remifentanil, a potent and ultrashort acting mu-opioid agonist. Sensitization was induced by heating forearm skin with a thermode at 45 degrees C for 5 min, immediately followed by application of 0.075% capsaicin cream for 30 min. Sensitization was rekindled four times at 40-min intervals with the thermode at 40 degrees C for 5 min. After each rekindling, areas of secondary hyperalgesia were measured, and the painfulness of thermal stimulation in normal skin with 45 degrees C for 1 min (long thermal stimulation [LTS]) was rated. Before and during the second rekindling, remifentanil 0.10 microg x kg(-1) x min(-1) or saline-placebo was infused for 35 min. Infusion of remifentanil reduced the areas of secondary hyperalgesia to 29--30% of baseline size compared with 75--83% during placebo. Similarly, remifentanil reduced the painfulness of LTS to 29% of baseline severity compared with 84% during placebo. Areas of secondary hyperalgesia and LTS painfulness returned to baseline levels by the time of the third rekindling, demonstrating rapid disappearance of remifentanil analgesia and possibly transient spontaneous opioid withdrawal hyperalgesia. Using the heat-capsaicin sensitization model, opioid analgesia and suppression of secondary hyperalgesia was reliably demonstrated without skin injury.